Mapping avalanches with satellites-Evaluation of performance and completeness - Hafner, Elisabeth D.; Techel, Frank; Leinss, Silvan; id_orcid:0 000-0002-4467-5793; Bühler, Yves (Copernicus, 2021)
pThe spatial distribution and size of avalanches are essential parameters for avalanche warning, avalanche documentation, mitigation measure design and hazard zonation. Despite its importance, this information is incomplete today and only available for limited areas and limited time periods. Manual avalanche mapping from satellite imagery has recently been applied to reduce this gap achieving promising results. However, their reliability and completeness have not yet been verified satisfactorily./p pIn our study we attempt a full validation of the completeness of visually detected and mapped avalanches from optical SPOT 6, Sentinel-2 and radar Sentinel-1 imagery. We examine manually mapped avalanches from two avalanche periods in 2018 and 2019 for an area of approximately 180 kmspan classCombining double low lineinline-formula2 around Davos, Switzerland, relying on ground-and helicopter-based photographs as ground truth. For the quality assessment, we investigate the probability of detection (POD) and the positive predictive value (PPV). Additionally, we relate our results to conditions which potentially influence avalanche detection in the satellite imagery./p pWe statistically confirm the high potential of SPOT for comprehensive avalanche mapping for selected periods (POD span classCombining double low lineinline-formulaCombining double low line 0.74, PPV span classCombining double low lineinline-formulaCombining double low line 0.88) as well as the reliability of Sentinel-1 (POD span classCombining double low lineinline-formulaCombining double low line 0.27, PPV span classCombining double low lineinline-formulaCombining double low line 0.87) for which the POD is reduced because mainly larger avalanches are mapped. Furthermore, we found that Sentinel-2 is unsuitable for the mapping of most avalanches due to its spatial resolution (POD span classCombining double low lineinline-formulaCombining double low line 0.06, PPV span classCombining double low lineinline-formulaCombining double low line 0.81). Because we ...